Tantangan Hukum dalam Pengelolaan Pariwisata Berkelanjutan di Raja Ampat: Antara Konservasi, Kearifan Lokal, dan Pembangunan - Nadya Rechtta Utami; Rahmad Ramadan (Lembaga Pengembangan Kinerja Dosen, 2025)
The Raja Ampat region, recognised as having some of the highest marine biodiversity in the world, faces challenges in sustainable tourism management. Issues such as environmental degradation due to tourism activities, land tensions between indigenous communities and investors, and mining expansion are complex. This study aims to assess the legal obstacles faced in maintaining the sustainability of the area, evaluate the role of local wisdom such as the practice of ‘sasi’ in natural resource conservation, and formulate a legal approach that favours local communities. Using a qualitative approach, the study combines a review of policy documents, data from civil society organisations, and juridical analysis of national regulations and customary practices. The results show that local wisdom systems make a real contribution to environmental conservation efforts, but have not received adequate legal recognition and protection. Regulatory disharmony, weak policy implementation, and low community involvement are the main inhibiting factors. The implications of this study emphasise the importance of harmonisation between national and local legal norms, as well as the need to strengthen the capacity of communities as the main actors in the preservation of sustainable tourism and regional cultural identity.